Development of WiFi-Bluetooth Communication Protocol (International Journal of Engineering and Computer Science, 2018)
Being different standards, translating packages sent from Bluetooth to Wi-Fi and vice versa is difficult and also the connections should not be broken or interrupted. Finding a right way to send and receive data is the need and also efficiency and reliability of the data is also necessary. Each protocol has its own associated hardware and software specification. Hence for communication between 2 devices with 2 different protocols is difficult. The system allows us to develop a network through which two powerful protocols can communicate with each other, even though the standards of the protocol are different.